Analisis Strategi Pengembangan Investasi Modal Pada PT. Mari Gadai Sejahtera Dalam Membantu Pembiayaan Masyarakat - Irna Della Br Ginting; Elisabeth Tamara Ratu Hutauruk; Nataline Simanjuntak; Tri Ayu Fadilah; Evi Syuriani Harahap (Sharing: Journal of Islamic Economics Management and Business, 2026)
The growing public demand for financing services has encouraged financing companies to increase their capital capacity through effective investment strategies. This study aims to analyze the capital investment development strategy implemented by PT. Mari Gadai Sejahtera in supporting community financing. The study used a qualitative approach with descriptive methods. Data were collected through interviews, observations, and documentation involving parties related to capital investment management and the company's financing activities. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results show that capital investment development is carried out through collaboration with investors, the use of digital technology to expand funding access, and the implementation of risk management through verification and assessment of collateral. These strategies have been proven to increase financing capacity, strengthen operational stability, and improve service quality to customers. Thus, effective capital investment management plays a crucial role in supporting business sustainability and the company's ability to meet community financing needs.